KOMMUNIKATIV-KOGNITIV QATNAS KÓZQARASÍNAN LEKSIKALÍQ KOMPETENCIYANÍŃ ÁHMIYETI - Xabibullaeva, Guljaxan Kengesbaevna (ILIM hám JÁMIYET, 2026)
The article examines the development of English lexical competence among students in grades 10-11 studying the Karakalpak language in the Republic of Karakalpakstan. The theoretical foundations of lexical competence, its structure and subcomponents (motivational, cognitive, practical, socio-cultural, reflexive) are analyzed.